Implementasi Keamanan Jaringan dengan Metode Security Profiles menggunakan Fortigate pada Komisi Aparatur Sipil Negara - Arbie, Fauzi Rizki; Raharjo, Mugi (LPPM STT Terpadu Nurul Fikri, 2024)
Current technological advances mean that all work carried out cannot be separated from the use of the internet network, both for accessing website pages to search for information and using applications as a medium for work. After conducting in-depth research, it was found that the network management and security used at the Pancoran State Civil Service Commission still uses default settings, causing less efficient use of the internet during work time, and is also vulnerable to attacks from outside. Network security is very important to protect data connected to the network both from the user and from the server side. Apart from that, administrators find it difficult to control access rights to web and applications that are not related to the needs of the organization or agency. To make it easier for administrators to control and improve network security, optimizing the use of the Fortigate 500E firewall is very necessary. By implementing the security profiles method on the Fortigate device, it will be easier to manage network traffic at preset hours and increase network security against irresponsible external attacks. By implementing the security profiles method, websites and applications that are not accordance with the organization’s objectives can be blocked automatically according to the preset time and network security at KASN Pancoran will be maintained. With this implementation, internet use at the State Civil Service Commission can be more stable by determining access priority for frequently used applications.